THE APPLICATION OF THE WASPAS METHOD WITH THE SWARA WEIGHTING METHOD APPROACH IN THE SELECTION OF SINGLE COLLEGE MONEY AID BUDIDARMA UNIVERSITY - Murdani; Lince Tomoria Sianturi (Sean Institute, 2021)
Decision making is very necessary in choosing the application for Single Tuition Assistance at Budidarma University because to get Single Tuition assistance is very limited, a selection is carried out before the data is sent to Tertiary Education Institutions I North Sumatra. Solving the problem above requires a way to make a decision on the Selection of Single Tuition Aid at Budidarma University with the WASPAS method. The reason for using the WASPAS method for making a decision can help and make it easier to do the selection. The weighting approach using the SWARA method, with a decision-making method so that the results help decision makers make decisions accurately. Keywords: Decision, Selection, Single Tuition Assistance, Waspas Method and Swara method